Assessing Pedagogical Diversity, Equity, and Inclusion in the Academy of Homiletics Special Issue Introduction (Homiletic, 2025)
Introduction to the Special Issue "Assessing Pedagogical Diversity, Equity, and Inclusion in the Academy of Homiletics."